2022
DOI: 10.3389/fmars.2022.853452
|View full text |Cite
|
Sign up to set email alerts
|

Review of Structure Types and New Development Prospects of Artificial Reefs in China

Abstract: Artificial reefs are beneficial to restore fishery resources and increase fishery production. Meanwhile, they play a significant role in improving ocean ecology and accelerating the evolution of fishery industries. Since they are generally affected by currents, waves, and other hydrological factors, the flow field around artificial reefs and their stabilities have become a research hotspot in recent years. Research on artificial reefs is a systematic process consisting of four aspects: Firstly, the significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Habitat diversity is another crucial aspect that in uences the community structure of marine organisms. Previous studies have shown that the complex structural design of ARs provides an ideal shelter for juvenile or small sh with limited swimming ability [34] . The profuse attached organisms on the ARs surface demonstrated a clear trapping impact on certain benthic sh or crustaceans [35] .…”
Section: Biological Community and The Related Environmental Factors O...mentioning
confidence: 99%
“…Habitat diversity is another crucial aspect that in uences the community structure of marine organisms. Previous studies have shown that the complex structural design of ARs provides an ideal shelter for juvenile or small sh with limited swimming ability [34] . The profuse attached organisms on the ARs surface demonstrated a clear trapping impact on certain benthic sh or crustaceans [35] .…”
Section: Biological Community and The Related Environmental Factors O...mentioning
confidence: 99%
“…Due to their limited height, the impact on the waters above the ARs may be relatively insufficient, and ARs were unable to fully utilize the entire water space. In order to improve comprehensive and three-dimensional development, it may be a considerable practice to combine bottom ARs in conjunction with floating ARs and jointly release them; it has been established that the combination of floating and bottom reefs complimented one another and impacted comprehensive usage [21].…”
Section: Would the Combined Ars Be Better?mentioning
confidence: 99%
“…Floating ARs are a feasible method for building artificial structures floating in the water [20]. They can potentially use marine space and display excellent antiwave as well as current performance, less constraint on seabed geology, and a feasible arrangement mode of multireef groups [21]; however, the research on the use of floating ARs to restore the ecological environment was still in its initial stage. Furthermore, there are gaps in evaluating the materials, configurations, and attraction effectiveness of floating ARs, which requires proper research.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial reefs are relatively easy to make, but efficacious placement depends on structure design, depth, distance from the shore, environmental and surrounding natural reef conditions, as well as wave and current conditions [28,[31][32][33]. Various materials have been used in the creation of artificial reefs, including concrete, wood, automobiles, or retired oil and gas platforms, each with benefits and drawbacks [34].…”
Section: Introductionmentioning
confidence: 99%